Alienation of Female Characters in the Movie Fair Play (2023) as Main Breadwinners in the View of Jaggar - Istinara, Terra; Sinaga, Hariati (Journal of Language and Literature, 2024)
The capitalist patriarchal system materializes in every aspect of life, even in the workplace, resulting in men and women's alienation. Unlike previous studies on women's alienation, this article examines the alienation of women as main breadwinners in a financial sector. Through film analysis, this article discusses the movie Fair Play released by Netflix in 2023. The movie focuses on a woman named Emily who gets a higher position than her fiancé in a securities company, causing jealousy. The movie Fair Play tries to distort the reality of how women are able to get higher positions in a male-dominated system. Drawing on Alison Jaggar's alienation theory, this article attempts to show how the form of alienation experienced by Emily as a woman is different from the alienation experienced by men in a capitalist patriarchal system. Using qualitative method in analyzing Fair Play movie scenes, the study reveals that alienation experienced by workers, whether female or male, is the result of an exploitative capitalist system. The article also argues that Emily experiences alienation of sexuality and intellectuality because of her femininity. This implies that women experience double standards because of the double burden caused by gender roles. It concludes that women experience alienation differently from men because of their gender. By eliminating of the concepts of masculinity and femininity, this alienation experienced differently by women can be overcome.